AUSTRALIAN ENGLISH AND THE PERCEPTION OF “AUSTRALIANESS” IN HENRY LAWSON’S SHORT STORIES - Scheidt, Déborah (Muitas Vozes, 2015)
Henry Lawson (1867-1922) occupies a central position in the so called “Australian bush tradition”. Lawson’s poems, essays and short stories have contributed to the specific perception of “Australianess” that famously characterized the 1890s but has left its marks in the way Australians see themselves today. This work examines the phenomenon of the appropriation of the English language by Lawson and his expert use of local aspects of English in short stories such as “The Drover’s Wife” and “A Love Story”. That appropriation can be verified in the author’s adoption of “Australianisms” as well as in writing style and the rhythm of his sentences, where the influence of popular literary modes, such as the “bush ballad” and the “yarn” can be detected. The combination of local themes and modes of expression with an objective, almost journalistic style outbalances mere provincial or parochial tendencies and makes of Lawon a precursor of the language of the modern short story even before it became mainstream in the rest of the world.